Peningkatan Prestasi Belajar Koloid Melalui Penerapan Strategi Pembelajaran Aktif Index Card Match Pada Siswa SMAN 2 Siak Hulu-Riau - Asmadi, Sri Haryati; Kamila, Yusli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The low achievement of students in SMAN 2 Siak Hulu on the subject ofColloids is caused by the lack of students’ involvement in learning the material. It needs astrategy that can make the students become active during the learning process. One of thestrategies that can activate the student is index card match active learning strategy. It hasbeen done a research in SMAN 2 Siak Hulu, Kampar, in XI science 1 class as an experimentclass and XI science 3 as a control class with pre-test and post-test design. The statistics datashowed that the value of t count was greater than t table which means that the hypothesis inthis study can be accepted, that is